Automorphisms of Zero Divisor Graphs of Square Radical Zero Commutative Unital Finite Rings - Lao Hussein Mude; Owino Maurice Oduor; Ojiema Michael Onyango (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
There has been extensive research on the structure of zero divisors and units of commutative finite rings. However, the classification of such rings via a well-known structure of zero divisors has not been done in general. More specifically, the automorphisms of such classes of rings have not been fully characterized. In this paper, we obtain a more complete illustration of the automorphisms of zero divisor graphs of finite rings in which the product of any zero divisor